Amor romântico evolutivo: o continuum rápido-lento e seus correlatos individuais e psicossociais - Loureto, Gleidson Diego Lopes (2021)
Abstract. This thesis aimed to test a taxonomy of romantic love (AR) based on the evolutionary framework of the Life History Theory (LHT) and investigate its relationships with individual, evolutionary and psychosocial variables. Five articles were performed. The Article 1 consisted of theoretical essay that presented the assumptions of LHT and proposed the so-called the Factor-K of RL which implies the slow-love continuum, comprising five proxies of evolutionary RL: restricted sociosexuality, appraisal and flexibility in context of conflicts, future orientation, disposition to parental investment and intimacy attachment style in relationships. In sum, derived from LHT, RL consists of a set of a certain survival strategies in face of evolutionary challenges varying along a fast-slow continuum. The Article 2 aimed to elaborate and investigate preliminary evidence of validity (i.e., content, internal structure and relationships with external variables) and reliability of the K-Love Scale of Romantic Love (KLS). Initially, via the content validity coefficient, the content validity of the five facets of the instrument was supported. An exploratory factor analysis indicated a one-dimensional structure of KLS, with adequate reliability. Regarding the evidence of convergent validation, the measure was positively correlated with measures of family stability in childhood, perceived authoritative parenting style and general life strategy (e.g., risk aversion, propensity for cooperation, etc.). The Article 3 consisted of a psychometric study and sought to investigate evidence of complementary validity and reliability of KLS. In Study 1 (n = 249), the hierarchical bifactor model provided evidence for the best model-data fit in contrast to one-factor and penta-factor structures. It has been demonstrated that KLS represented a combined functioning (i.e., a global fact, the K-Factor) of the five facets that comprises the evolutionary RL. In Study 2 (n = 203), KLS was negatively related to intentions towards infidelity and attitudes towards polyamory and positively to self-esteem; such results extend the evidence of convergent validity of the measure. The Article 4 tested the predictive power of KLS in explaining satisfaction and conflicts in romantic relationships. In Study 1 (n = 205), EFKA presented incremental validity in explaining satisfaction in relationships compared to two classic RL models. In Study 2 (n = 251), KLS predicted constructive responses to the conflict. Additionally, we showed the moderating effect of interactive values and the trait of psychopathy in the KLS-constructive responses link: when medium and high on interactive values, individuals react more constructively to conflict; in turn, when medium and high on psychopathy, individuals employ more destructive responses. Finally, in the Article 5 we performed an experimental study (2x2x2; n = 212) with a mixed design in order to test the effect of romantic traits (fast love vs. slow love) and the endorsement of human values (personal values vs. social values) on the desirability of a romantic target as a long-term partner. As expected, individuals with “slow love” traits and endorsing social values were rated as more desirable as partners in a long-term relationship, as predicted by evolutionary assumptions. In short, it is concluded that the objectives were achieved in view of the proposition of an evolutionary model of theoretically oriented RA. In sum, the current objectives were achieved by proposing an evolutionary model of RL that consists in a theoretically-driven approach. Furthermore, the current thesis contributes to the articulation of intra-individual, evolutionary and psychosocial aspects in the understanding of human romantic interactions, in line with the growing integration between the fields of social psychology and evolutionary sciences.